2001
DOI: 10.1177/00220345010800030601
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Properties of the Human Temporomandibular Joint Disc

Abstract: The cartilaginous intra-articular disc of the human temporomandibular joint shows clear anteroposterior variations in its morphology. However, anteroposterior variations in its tissue behavior have not been investigated thoroughly. To test the hypothesis that the mechanical properties of fresh human temporomandibular joint discs vary in anteroposterior direction, we performed dynamic indentation tests at three anteroposteriorly different locations. The disc showed strong viscoelastic behavior dependent on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(124 citation statements)
references
References 22 publications
8
112
2
Order By: Relevance
“…Maximum peak of the von Mises stress observed in the intermediate zone was also mentioned in previous studies (10,11,14,22). And an anatomical study with a cadaver showed maximum pressure signals during mandibular movements in discs located in the intermediate zone (23).…”
Section: Fm Ferreira Et Alsupporting
confidence: 79%
See 1 more Smart Citation
“…Maximum peak of the von Mises stress observed in the intermediate zone was also mentioned in previous studies (10,11,14,22). And an anatomical study with a cadaver showed maximum pressure signals during mandibular movements in discs located in the intermediate zone (23).…”
Section: Fm Ferreira Et Alsupporting
confidence: 79%
“…The articular disc was shown to have both viscoelastic and hyperelastic properties and undergoes large deformation (22). Therefore, another form of representation is to consider soft tissues as viscoelastic structures.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of chondrocyte-like cells in the center of the TMJ disc compared with the periphery corresponds well to the elevated levels of chondroitin sulfate and higher compressive stiffness reported for the center of the disc. [20][21][22][23][24] Moreover, the higher relative number of chondrocyte-like cells on the inferior surface compared with the superior surface of the disc may shed light on functional differences between the inferior and superior joint spaces of the TMJ. These results may suggest a more mechanically demanding environment in the inferior joint space, which is supported by the observed increased levels of degeneration in the inferior space in cases of TMJ disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the reaction forces attempt to perform a closing jaw rotation about this axis (Koolstra and van Eijden, 1995). The cartilaginous temporomandibular joint disc and the cartilage lining of the articular surfaces are deformable, with a finite and non-linear elasticity (Beek et al, 2001). This elasticity causes the joint reaction force to be dependent on the deformation.…”
Section: Articular Surfacesmentioning
confidence: 99%